Papaya Consumption and its Effect on Breast Milk Production in Post Partum Women : Study at Mabu’un Health Centre - Rina Lasmilawati; Nila Widya Keswara; Rani Safitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Adequate breast milk production is crucial for the health and development of newborns, yet many postpartum mothers face challenges in breastfeeding. Various factors, such as diet, nutritional status, and stress, can significantly influence milk production. Young papaya is known to contain lactagogum, which can stimulate the hormones prolactin and oxytocin, both of which play a vital role in enhancing breast milk production. This study aimed to examine the effect of young papaya consumption on breast milk production among postpartum women. A quantitative design with a quasi-experimental approach, specifically a post-test control-only group design, was used for this study. The sample consisted of 20 postpartum women, who were divided into two groups: the treatment group (consuming young papaya) and the control group. Data were collected through a questionnaire, and the analysis was conducted using Fisher's exact test with SPSS software. The results revealed that 70% of the mothers experienced smooth breast milk production, with the treatment group (those who consumed young papaya) reporting significantly higher levels of smooth milk production compared to the control group. Fisher's exact test showed a statistically significant association between the consumption of young papaya and the smoothness of breast milk production (p=0.005). In conclusion, the consumption of young papaya has a positive effect on increasing breast milk production in postpartum women. The papain enzyme present in young papaya appears to stimulate the hormones essential for milk production. Therefore, increasing awareness and education about the benefits of young papaya consumption as a lactagogue can play a significant role in supporting successful breastfeeding. Further studies with larger sample sizes are recommended to validate these findings and explore the long-term effects of young papaya consumption on lactation.